2014
DOI: 10.1155/2014/512680
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Characteristics and Spacing in Primary Dentition: A Gender Comparative Cross-Sectional Study

Abstract: Context. Occlusion in primary teeth varies among children of different populations and races. Aim. To assess and compare the occlusal characteristics and spacing in primary dentition among 3–6-year-old Dravidian children. Materials and Methods. The study included 2281 school going children. The primary molar relation, canine relation, overjet, and overbite were assessed using Foster and Hamilton criteria. Spacing conditions were registered according to Kisling and Krebs criteria. Results. The flush terminal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
14
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 22 publications
9
14
2
Order By: Relevance
“…This study showed Class I canine relationship to be the most common in more than half of the children while the least common was the class III canine relationship among 19% children. Similar findings was seen in studies conducted by Bahadure et al 12 , Shah et al 6 and Vegesna et al 3 while contradictory findings were reported in Finnish children where class II canine relationship was found to be more common. 13 In this study majority 77% of the children had ideal overjet ,increased overjet was found among 17.4% while 5.6 % had reverse overjet which were in agreement to studies done by Oteyumi et al 10 , Shah et al 6 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This study showed Class I canine relationship to be the most common in more than half of the children while the least common was the class III canine relationship among 19% children. Similar findings was seen in studies conducted by Bahadure et al 12 , Shah et al 6 and Vegesna et al 3 while contradictory findings were reported in Finnish children where class II canine relationship was found to be more common. 13 In this study majority 77% of the children had ideal overjet ,increased overjet was found among 17.4% while 5.6 % had reverse overjet which were in agreement to studies done by Oteyumi et al 10 , Shah et al 6 .…”
Section: Resultssupporting
confidence: 88%
“…As seen in the study, Ideal overbite was seen among majority (78%) of the children, various studies showed similar findings. 3,6 Only four (0.9%) children in the study had anterior openbite as reported in other study done in Tanzanian and Finnish children (8%). 14 The study has few limitations as data could have included specific sides, and in detail findings as per arch wise, gender wise for spacing.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The second elderly molar relation is also called the terminal plane, the mesiodistal relation between the distal surface of the upper and lower jaw molars of the upper jaw which is assessed when the primary tooth is in the centric occlusion position. 5,[7][8][9][10]22,24 The relation can be classified into three types according to Baume, which are flush terminal plane, mesial step, and distal step. 16 This study focuses on the examination of the second primary molar relationship performed when the tooth is in centric inclusion position by using an intraoral mirror.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion criteria of the study subjects were, preschool age students in four State Kindergarten of Banda Aceh, with parents were willing to sign informed consent, and the first teeth were still complete; none of the missing primary teeth. 5,10,22,23 Criteria exclusion of the study is a subject of research that is not willing to follow the research and if the subject has mesial step occlusion on one side and the other side has a distal occlusion step.…”
Section: Methodsmentioning
confidence: 99%